The Effect of Adding Cellulose on the Mechanical and Chemical Properties of the Cement - A. Addullah, Nadhim; A. AL.ghanim, Hameed; k. Husain, Haleem; A. Abood, Mothana (University of Thi-Qar Journal of Science, 2009)
In this study we focused on adding cellulose found in the covers of sun flower andthis adding was in form of different ratio and constant size of these additive to thematrix of Iraqi cement ( Om Qasar factory for cement ) .the prepared sampleswas in form of cubic and evaluated as they were treated different ( watertreatment, moisture treatment dry treatment ). All the prepared samples had aproportion of (3 /1 ) cement to sand and in the form of cubes with aside ( 50 mm ) long .theyalso had the the weight –rate of the added cellulose to the cement which was ( 1%- 5%) .The obtained results showed that the cement mixture that had the weight rate of5% is the best as it has good mechanical properties ( flexural strength , splittingtensile, compressive strength ) .These properties have been used to study theresistance of the modified cement to the chemical agents that attack cement andconcrete.